KELENGKAPAN ANTENATAL CARE (ANC) DENGAN KEJADIAN BBLR - Neli Sunarni; Elis Noviati; Rudi Kurniawan; Nur’aeni Mulyati (LPPM STIKes Muhammadiyah Ciamis, 2018)
Low Birth Weight Babies (LBW) are babies born less than 2,500 grams. The LBW birth rate at the Ciamis District Regional General Hospital is quite high. One of the efforts to reduce the incidence of LBW is to improve the antenatal care at least 4 times during pregnancy. This study uses a type of quantitative analytical research using the Cross Sectional approach. The population in the study were all mothers who gave birth at the Ciamis District Regional General Hospital. The study sample was 30 people. The results showed that the completeness of antenatal care (ANC) was mostly in complete category, namely 17 people (56.7%). LBW incidence was mostly in the category of LBW as many as 17 people (56.7%). There is a relationship between the completeness of antenatal care (ANC) and the incidence of low birth weight because the values of ?> ? values (0.05> 0.007) and incomplete antenatal care (ANC) have a chance of 10.083 (10) times greater than the incidence of low birth weight. The conclusion in this study is that there is a significant relationship between the completeness of antenatal care (ANC) and the incidence of LBW at the District General Hospital of Ciamis Suggestions are expected to improve ANC services by providing counseling to patients about the importance of ANC visits The conclusion in this study is that there is a significant relationship between the completeness of antenatal care (ANC) and the incidence of LBW at the District General